Single embryo transfer for all. (November 2018) - Cutting, Rachel
Abstract: There is a global recognition of the need to reduce multiple pregnancies following assisted reproductive technology. Complications of multiple pregnancies can be simply avoided by replacing one embryo at a time. Most policies to reduce the number of double or higher order embryo transfers involve predicting which patients are at most risk by using a multiple birth minimisation strategy. These frequently consider factors such as patient age, previous treatments and embryo quality. However, with improvements in methods of embryo culture, embryo selection and cryopreservation, this chapter will question whether, at present, it is time to move to single embryo transfer (SET) for all. Highlights: Elective single embryo transfer (eSET) is an effective strategy to reduce multiple pregnancies. Multiple pregnancies pose a significant risk to mother and baby. Technological advances may improve embryo selection to further encourage eSET.